ESSENCE OF ECONOMICAL SAFETY SYSTEM OF FUEL AND ENERGY COMPLEX AS ONE OF THE TYPES OF A COMPLEX SOCIAL-ECONOMICAL SYSTEM - Dmytro Busariev (World Science, 2019)
The main purpose of the article is to define the essence of the economic security system of the fuel and energy complex. The essential features of the concept «system» are defined. The concept of «system of economic security» in the context of essential features has been formed as a divergence. The main approaches to the interpretation of the concept of «economic security system» are defined. The interdependence of the hierarchy of goals of the economic security system of a complex socio- economic system is determined.